Effects of fifteen species of green manure on water-holding capacity and nematode control of a dark-red latosol under "Cerrado' vegetation - Resck, D. V. S.; Sharma, R.D.; Pereira, J. (Pesquisa Agropecuaria Brasileira, 2014)
The effects of fifteen species of green manure on water-holding capacity and nematode control were observed in a dark-red Latosol; The test was conducted during the years of 1971/78 and 1918/79. Green manure was cultivated in first year and incorporated in March of 1978. A soybean test-crop was planted in the second year, using the UFV-1 cultivar. Water-holding capacity at 1 atm and nematode population were evaluated during this period. Soil water-holding capacity increased with all green manure studied until August of 1978, varying from 0.21 to 0.24 cm3 of water per cm of soil except in plots containing Stizolobium aterrimum, deeringianum and S. niveum. This increase of soil-water retention, varying from 0.21 to 0.26 cm of water per cm3 of soil, occurred until October of 1978. After the time these values decreased until February of 1979 and then increased again from 0.19 to 0.25 cm of water per cm of soil. After the incorporation, nematode population drastically decreased in all treatments until the planting of soybean. Soybean yields average were 2,500 kg/ha, although no manure had been used in the planting.
Keywords: available soil water; incorporation of green manure